2020
DOI: 10.1021/acs.jpcc.9b10453
|View full text |Cite
|
Sign up to set email alerts
|

Excitation Energy Transfer/Migration between Tris(8-hydroxyquinoline) Aluminum and Poly[2-methoxy-5-(2-ethylhexyloxy)-1,4-phenylenevinylene] in Chloroform

Abstract: Excitation energy transfer/migration between fluorescent electron transport molecule tris(8-hydroxyquinoline) aluminum (donor) and fluorescent hole transport polymer poly[2-methoxy-5-(2-ethylhexyloxy)-1,4-phenylenevinylene] (acceptor) were studied in chloroform solution at room temperature using steady-state and time-domain fluorescence measurements. The blend of this pair is widely used in the fabrication of organic light-emitting diode. The considerable overlap integral between the emission spectrum of donor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 46 publications
1
10
0
Order By: Relevance
“…In our early study of FRET in the AlQ 3 –MEHPPV system, we found that at a low acceptor concentration, energy migration and energy transfer influence the kinetics of excitation energy transfer, resulting in a significant difference in the observed and calculated value of the FRET parameters. The excited-state decay time analysis confirms the effect of intrachain and interchain interactions during nonradiative excitation energy transfer in the donor–acceptor solution …”
Section: Introductionsupporting
confidence: 52%
See 2 more Smart Citations
“…In our early study of FRET in the AlQ 3 –MEHPPV system, we found that at a low acceptor concentration, energy migration and energy transfer influence the kinetics of excitation energy transfer, resulting in a significant difference in the observed and calculated value of the FRET parameters. The excited-state decay time analysis confirms the effect of intrachain and interchain interactions during nonradiative excitation energy transfer in the donor–acceptor solution …”
Section: Introductionsupporting
confidence: 52%
“…Förster resonance energy transfer (FRET) is one of the most popular methods in organic electronics to increase the efficiency of electroactive parts. The Förster theory is based on the concept of treating a fluorophore as an oscillating dipole, which can nonradiatively transfer excitation energy to another dipole with a similar resonance frequency through the long-range dipole–dipole coupling and is a distance-dependent phenomenon (depends on the sixth power of donor–acceptor separation) . The theory is applicable for the media in which the molecules are either stationary or the molecular diffusion and energy migration is sufficiently low.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…FRET between fluorescent organic semiconductor donor−acceptor systems thus plays a vital role in increasing the efficiency of devices, including organic photovoltaic (OPV), organic lightemitting diodes (OLED), solar cell, etc. [6][7][8][9]21,22 EET between different fluorescent organic semiconducting polymers or molecules is reported in the literature to explain the performance and characterization of various electronic devices. 1−4 FRET pair of [poly(9,9-dioctylfluorene-alcoholbenzothiadiazole] (F8BT) and P3HT (poly-3-hexylthiophene) in a blend film show that singlet excitons of F8BT transfer their excitation energy very fast within a picosecond to P3HT polymer.…”
Section: Introductionmentioning
confidence: 99%
“…However, for higher acceptor concentration, EET follows the Forster mechanism of energy transfer. 9 In a recent work, 10 we reported the effect of diffusion on FRET between an n-type donor (AlQ 3 ) and a p-type acceptor 6,13-bis(triisopropylsilylethynyl) pentacene (TIPS-P) in a chloroform solution. This pair followed energy transfer by donor diffusion and an exciplex formation at low acceptor concentration.…”
Section: Introductionmentioning
confidence: 99%